EFEKTIVITAS PENGGUNAAN MEDIA PROYEKSI DIAM DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM SISWA KELAS X DI SMA NEGERI 10 ACEH BARAT DAYA - Mutiya, Cut Virda; Tanzilul Authar; Hermanita (STIT Muhammadiyah Aceh Barat Daya, 2025)
The use of instructional media plays a vital role in delivering lessons to students, aiming to boost their motivation and academic achievement. Teachers need to effectively utilize media and resources suited to students' characteristics and subject matter to achieve learning objectives. However, many teachers lack the skills to use instructional media or rarely incorporate it into their teaching, particularly in Islamic Religious Education, impacting students' learning outcomes. This study examines: (1) the effectiveness of using static projection media to improve Islamic Religious Education outcomes among grade X students at SMAN 10 Aceh Barat Daya; (2) barriers to its use; and (3) efforts by teachers to enhance its effectiveness. Using quantitative methods with a sample of 20 students, data was collected via observation, questionnaires, interviews, and descriptive statistical analysis. Results indicate the media’s effectiveness (p < 0.05, t-value > t-table), barriers such as limited projectors and unsuitable content, and teacher efforts to create engaging materials and improve technological skills.